MEASURING THE IMPACT OF SUPPLY CHAIN PRACTICES ON ORGANIZATIONAL PERFORMANCE - Farah Aljubairi; Hesham Mugharbil (PalArch's Journal of Archaeology of Egypt / Egyptology, 2021)
The phenomenon of supply chain management is not new to the world, and there is a great deal of research into its relevance and timely use in business processes. The process of getting the raw material to deliver the goods and services to the customer is all part of the supply chain system. It is one of the most important parts of the business process of the company that connects the company from the outside world. Thus, this work has examined the supply chain management practices impact on the organizational performance in Saudi Arabia. This work was carried out using quantitative research method. The data collection was done using survey questionnaire. The sample population comprised of 30 people from Panda supermarket. The data were analyzed using SPSS software. The key results have shown that is positive relationship and impact between supply chain management practices and organizational performance. Thus, it is deduced that supply chain management is important for organizational performance.